English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

1.(x+5)(x+2)

2.(x-2)(x-2)

3.(x+5)(-12)

4.(3c-4d)(2c+5d)

5.(5x-3)(3x-8)

2007-07-05 07:41:20 · 6 answers · asked by brandon_burdette 1 in Science & Mathematics Mathematics

6 answers

2.(x-2)(x-2) = x^-4x+4
3.(x+5)(-12)= -12x -60

4.(3c-4d)(2c+5d) = 6c^2 +7cd -20d^2

5.(5x-3)(3x-8) = 15x^2-49x +24

2007-07-05 07:48:21 · answer #1 · answered by ironduke8159 7 · 0 0

Use the FOIL method. First, Inside, Outside, Last.
1) F x*x=x^2
O x*2=2x
I 5*x=5x
L 5*2=10
add like terms; x^2+7x+10

4) F 3c*2c=6c^2
O 3c*5d=15cd
I -4d*2c=-8cd
L -4d*5d=-20d^2
6c^2+7cd-20d^2

Follow these examples; you should be able to finish the others.

2007-07-05 07:47:29 · answer #2 · answered by hrhbg 3 · 0 0

1.(x+5)(x+2)
x^2 +7x+10

2.(x-2)(x-2)
x^2 -4x+4

3.(x+5)(-12)
-12x-60

4.(3c-4d)(2c+5d)
6c^2 -20d^2 +7cd

5.(5x-3)(3x-8)
15x^2-49x+24

2007-07-05 07:45:14 · answer #3 · answered by sweet n simple 5 · 0 0

You have to break these into parts: . 1. (x-4)(x+6) is the same as x(x+6) + -4(x+6) . so, you get x^2 + 6x + -4x -24 . Then you add the x^2's up, the x's up, etc... . (x-4)(x+6) = x^2 + 6x -4x -24 = x^2 + 2x -24 . Your second answer is right, though people usually put the higher powers (ie x^2) first and lowest powers last. . . . 2. (x-10)(x+10) = x(x+10) + -10(x+10) = x^2+10x -10x -100 . (x-10)(x+10) = x^2 - 100 Tell you a trick, when you have one like this, say (whatever + something)(whatever - something) it will always come out as whatever^2 - something^2 . . . 3. (6y-3)(6y+3) = 6y(6y+3) + -3(6y+3) = 36y^2 +18y -18y -9 . (6y-3)(6y+3) = 36y^2 - 9 . This is the same trick as above . . . 4. (y-5)^2 = (y-5)(y-5) = y(y-5) + -5(y-5) = y^2-5y + -5y+25 . (y-5)^2 = y^2 -10y + 25 You just gotta remember that squared means - multiplied times itself - then do that :) . . . 5 (3a+4b)^2 = (3a+4b)(3a+4b) (just like 4) (3a+4b)^2 = 3a(3a+4b) + 4b(3a+4b) = 9a^2+12ab + 12ab+16b^2 (3a+4b)^2 = 9a^2 + 24ab + 16b^2 . . . 6 (2x+y)(x^2+xy+y^2) = 2x(x^2+xy+y^2) + y(x^2+xy+y^2) = 2x^3+2x^2y+2xy^2 + x^2y+xy^2+y^3 now, collect all the terms that are the same (in this case x^2y & xy^2) . = 2x^3 + 3x^2y + 3xy^2 + y^3 .

2016-05-18 23:56:29 · answer #4 · answered by Anonymous · 0 0

Use FOIL to multiply binomials.
1. F x^2
O 2x
I 5x
L 10
Add them up: x^2 +7x +10
2. x^2 - 4x + 4
3. -12x - 60 (distributive property)
4. 6c^2 + 15cd - 8cd - 20d^2 = 6c^2 + 7cd - 20d^2
5. 15x^2 - 49x + 24

2007-07-05 07:48:17 · answer #5 · answered by MathProf 4 · 0 0

1. x^2 + 7x + 10

2. x^2 -4x +4

3. -12x -60

4. 6c^2 +7cd -20d^2

5. 15x^2-49x -24

2007-07-05 07:48:28 · answer #6 · answered by Jon M 3 · 0 0

fedest.com, questions and answers